Influence of Helicobacter pylori Infection on Metabolic Syndrome in Old Chinese People - Wen Yang; Cunfu Xuan (Gastroenterology Research and Practice)
Background. H. pylori infection is one of the most common chronic infectious inflammatory diseases worldwide and is also a risk factor for atherosclerosis. Patients with metabolic syndrome are known to be at increased risk for atherosclerosis. The aim of our study was to assess the effects of H. pylori infection on serum lipids, body mass index (BMI), and metabolic syndrome in old Chinese people. Material and Method. A total of 191 (133 males and 58 females, aged 73.19±11.03 years) people who had gastroscopy examination in our hospital were divided into H. pylori-positive group (n=80) and H. pylori-negative group (n=111). H. pylori infection was diagnosed by rapid urease test. Results. Patients with H. pylori infection had higher BMI and fasting glucose levels and incidence of metabolic syndrome (p<0.01). It was found that BMI (p<0.01, OR 74.469), H. pylori infection (p<0.01, OR 5.427), total cholesterol (p<0.01, OR 15.544), and diabetes mellitus (p<0.01, OR 23.957) were significantly associated with the risk of metabolic syndrome by binary logistic regression analysis. Conclusions. Patients with H. pylori infection had higher BMI and fasting glucose levels and had incidence of metabolic syndrome.